Nuclear factor-κB regulates expression of platelet phospholipase C-β2 (PLCB2) - Mao, Guangfen; Jin, Jianguo; Kunapuli, Satya P.; Rao, A. Koneti (Thrombosis and Haemostasis, 2016)
Phospholipase C (PLC)-β2 (gene PLCB2) is a critical regulator of platelet responses upon activation. Mechanisms regulating of PLC-β2 expression in platelets/MKs are unknown. Our studies in a patient with platelet PLC-β2 deficiency revealed the PLCB2 coding sequence to be normal and decreased platelet PLC-β2 mRNA, suggesting a defect in transcriptional regulation. PLCB2 5’- upstream region of the patient revealed a heterozygous 13 bp deletion (-1645/-1633 bp) encompassing a consensus sequence for nuclear factor-κB (NF-κB). This was subsequently detected in three of 50 healthy subjects. To understand the mechanisms regulating PLC-β2, we studied the effect of this variation in the PLCB2. Gel-shift studies using nuclear extracts from human erythroleukaemia (HEL) cells or recombinant p65 showed NF-κB binding to oligonucleotide with NF-κB site; in luciferase reporter studies its deletion reduced PLCB2 promoter activity. PLCB2 expression was decreased by siRNA knockdown of NF-κB p65 subunit and increased by p65 overexpression. By immunoblotting platelet PLC-β2 in 17 healthy subjects correlated with p65 (r=0.76, p=0.0005). These studies provide the first evidence that NF-kB regulates MK/platelet PLC-β2 expression. This interaction is important because of the major role of PLC-β2 in platelet activation and of NF-κB in processes, including inflammation and atherosclerosis, where both are intimately involved.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Megakaryocytess; nuclear factor-κB; phospholipase C-β2; platelet function defect; platelets